Immunonutrition for traumatic brain injury in children and adolescents: protocol for a systematic review and meta-analysis - Linan Zeng; Lingli Zhang; Hailong Li; Rong Peng; Lijun Yang; Xinwei Chen; Zhenyan Bo (BMJ Open)
Introduction Traumatic brain injury (TBI) is the leading cause of paediatric trauma death and disability worldwide. The ‘Guidelines for the Management of Severe Traumatic Brain Injury (Fourth Edition)’ recommend that nutritional goals should be achieved within 5–7 days of injury. Immune-enhancing nutrition or immunonutrition, referring to the addition of specialised nutrients, including glutamine, alanine, omega-3 fatty acids and nucleotides, to standard nutrition formulas, may improve surgical outcomes in the perioperative period. However, the role of immune-enhancing nutritional supplements for patients with paediatric TBI remains unclear. We will conduct a systematic review to determine the efficacy and safety of immunonutrition for patients with paediatric TBI and provide evidence for clinical decision-making.Methods and analysis Studies reporting immune-enhancing nutrition treatments for patients with paediatric TBI will be included. Outcomes of interest include the length of hospital stay, wound infections, all-cause mortality, non-wound infection, including pneumonia, urinary tract infection and bacteraemia, and the reports adverse events. Duration of follow-up has no restriction. Primary studies consisting of randomised controlled trials (RCTs) and non-RCTs will be eligible for this review, and only studies published in English will be included. We will search the Medline, Embase and Cochrane Library databases from their inception dates to January 2020. We will also search clinicaltrials.gov and the WHO International Clinical Trials Registry Platform for additional information. Two reviewers will independently select studies and extract data. Risk-of-bias will be assessed with tools based on the Cochrane risk-of-bias criteria and Newcastle-Ottawa Quality Assessment Scale. A meta-analysis will be used to pool data when there are sufﬁcient studies with homogeneity. Heterogeneity of the estimates across studies will be assessed; if necessary, a subgroup analysis will be performed to explore the source of heterogeneity. The Grades of Recommendation, Assessment, Development and Evaluation method will be applied to assess the level of evidence obtained from this systematic review.Ethics and dissemination The proposed systematic review and meta-analysis will be based on published data, and thus ethical approval is not required. The results of this review will be published.PROSPERO registration number CRD42020154814.